Pengaruh Media Simpan dan Letak Biji dalam Buah terhadap Viabilitas Benih Kakao (Theobroma cacao L.) - NI KADEK KRISNA JAYANTI; I MADE SUKEWIJAYA; IDA AYU MAYUN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
The Effect of Storage Media and Seeds Location in Fruit to the Viability of Cocoa Seeds (Theobroma cacao L.) One of the productivity of cacao plants is determined by the seeds. Cacao seeds are classified as recalcitrant seed that do not have dormancy period, so they need special storage technique and proper seeds selection to maintain their viability. This study aims to determine the effect of storage media and seeds location in fruit to the viability of cacao seeds. This study used factorial completely randomized design consisting of 2 factors with 3 repetitions. The first factor is storage media, consists of 3 levels (cocopeat 100%, cocopeat 50%+husk 50%, cocopeat 50%+saw dust 50%). The second factor is the seed location in fruit, consists of 3 levels (first, middle, and end of fruits). The observed variable includes the percentage of moldly seeds in the storage, seed moisture content, rate of germination, vigor index, germination, hypocotyl length, epycotyl length, and number of leaves. The result of the study showed that storage media very significally affected to the percentage of moldy seeds in the storage, seed moisture content, vigor index, germination, hypocotyl length, and significally affected to the rate of germination. The seed location significally affected to seed moisture content, vigor index, germination, and epycotyl length. There is no significant interaction between storage media treatment and seed location to all benchmark of cacao seed viability observed. The good treatment is in the cocopeat storage media 50%+saw dust 50% with the seeds location in the first and middle of fruit.